Pea protein-based pickering emulsions: Mechanistic insights into its modification and innovations for food applications - Nita Aryanti; Alifia Rizki Adina; Aininu Nafiunisa; Dyah Hesti Wardhani (Journal of Agriculture and Food Research)
Pickering emulsions, an emulsification technique introduced over a century ago, have recently emerged as a promising solution in food science, driven by the global shift towards natural and sustainable ingredient use. Unlike traditional surfactants, solid particles offer distinct advantages as emulsion stabilizers, with their efficiency determined by factors such as wettability, particle size, and surface characteristics. Among these stabilizers, pea protein has gained attention for its renewable nature and compatibility with food systems, making it an excellent candidate for sustainable formulations. However, in its unmodified state, pea protein often struggles to achieve the stability required for advanced applications, highlighting the need for strategic enhancements. This review explores key modification methods for pea protein, including ultrasonication (physical), chemical reactions with reducing sugars, and enzymatic hydrolysis, while also examining complexation mechanisms and factors that improve its stabilizing properties in Pickering emulsions. Pea protein-based Pickering emulsions have demonstrated exceptional versatility, paving the way for innovative food applications such as 3D-printed foods, plant-based meat alternatives, and dairy substitutes. By consolidating recent breakthroughs, this study underscores the transformative potential of pea protein as a cornerstone for sustainable food technologies. It highlights critical opportunities for advancing its applications in diverse food products.